Evaluating the Predictive Validity of Objective Structured Clinical Examination (OSCE) Scores for Future Clinical Performance Among Final-Year Medical Students in Pakistan: Predictive Validity of OSCE Scores for Future Clinical Performance - Akhwand, Madiha; Abdullah, Zainab; Hassan, Bilqis; Amin, Sarah; Saleem, Sadaf; Gohar, Humera (Pakistan Journal of Health Sciences, 2025)
The Objective Structured Clinical Examination (OSCE) is widely used in medical education to assess students’ clinical skills. However, its ability to predict future clinical performance, known as predictive validity, remains debated. Objectives: To evaluate the predictive validity of OSCE scores for subsequent clinical performance among final-year medical students. Methods: This retrospective cohort study was conducted at a tertiary medical college in Pakistan. Data were collected for 80 final-year MBBS students, including total OSCE scores and domain-wise performance. Subsequent clinical performance was assessed using clerkship scores in Internal Medicine and Surgery, along with Mini-CEX, DOPS, 360-degree evaluations, and supervisor ratings. Pearson’s correlation and multiple linear regression were used to examine associations. Results: The mean OSCE score was 72.7 ± 7.8. Only the Internal Medicine Clerkship Score showed a statistically significant negative correlation with OSCE performance (r = –0.224, p=0.046). However, the effect size was small, and the clinical significance of this finding is questionable. The association may reflect random variation or unmeasured confounding and should be interpreted with caution. No other clinical outcomes showed significant correlations. Regression analysis revealed that none of the OSCE domains significantly predicted final clerkship scores. Conclusions: OSCE scores showed limited predictive value for subsequent clinical performance in this cohort. The results highlight the need to interpret statistically significant but weak associations with caution. Multimodal assessments combining OSCEs with workplace-based tools may offer a more comprehensive evaluation of clinical competence.